Geodynamic constraints of Patagonia, Tierra del Fuego and Antarctic Peninsula crustal blocks within the Terra-Australis Orogen - Rojo Martel, Diego Andres; Calderón, Mauricio; Ghiglione, Matias
After the consolidation and break-up of Rodinia, the reorganization of the tectonic plates favored the amalgamation of Gondwana, thus important sedimentary basins reported in it are somehow linked to the Brasilian / Pan African orogeny. The sedimentary basins of southern Gondwana and their respective detrital zircon U-Th-Pb can be used as a proxy to give light to the close relationship among the orogenic phases (e.g., Grenville, Brasiliano/Pan African, Pampean, Famatinian, Gondwana), sedimentary basins and igneous and metamorphic belts. We use an approach analyzing the presence of Neoproterozoic to upper Paleozoic magmatic, metamorphic, and sedimentary rocks along Gondwana and the patterns of detrital zircon exhibited in the fossil basins to elucidate an important part of the history and geological evolution of this supercontinent. Fil: Rojo Martel, Diego Andres. Universidad de Buenos Aires; Argentina Fil: Calderón, Mauricio. Universidad del Desarrollo; Chile Fil: Ghiglione, Matias. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina XVI Congreso Geológico Chileno. Chile Sociedad Geológica de Chile